IMPLEMENTASI CUSTOMER RELATIONSHIP MARKETING PADA PELAYANAN KELUHAN PELANGGAN PT. PLN (PERSERO) - Vahlepy, Donna; Wardianto, Kussuyatmono Bagus (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2024)
Every company wants to expand its current business unit. Paying attention to the customer loyalty factor is one of the actions that can be taken to improve the business unit. At PT. PLN (Persero) Way Halim Customer Service Unit, intends to analyze and then show the effect of trust, company commitment, communication, and conflict handling on customer loyalty. Informants in this study found 8 people, which is a descriptive study with a qualitative approach. The results of the study show that (1) the Trust Indicator provides good service quality, timeliness, and integration. (2) Commitment indicators provide service guarantees in accordance with the level of service to customers. (3) Communication indicators can provide convenience for customers to obtain information through various media such as call center 123 and the PLN mobile application. (4) In an effort to increase customer loyalty, the company PT. PLN (Persero) Way Halim Customer Service Unit is concerned with issues of trust, company commitment, communication, and conflict handling because all these aspects have an impact on customer loyalty.